Red Laser-Activated Silver Nanoparticles from Green Synthesis Extract of Butterfly Pea for Antimicrobial Photodynamic Therapy Against Staphylococcus aureus - Astuti, Suryani Dyah; Farhah, Ghinaa Rihadatul Aisy; Salwa, Umaimah Mitsalia Ummi; Aisya, Rohadatul; Zaidan, Andi Hamim; Yaqubi, Ahmad Khalil (Indonesian Journal of Tropical and Infectious Disease, 2024)
This study investigated the potential of photodynamic therapy (PDT) using green-synthesized silver nanoparticles (AgNPs) derived from butterfly pea extract (Clitoria ternatea L.) to combat Staphylococcus aureus (S. aureus). The use of a red diode laser as a method for enhancing the antimicrobial activity of AgNPs presents a novel approach to treating bacterial infections.  The red diode laser is crucial, as it activates the AgNPs, enhancing their antimicrobial properties. This combination of light, natural extract, and nanoparticles underscores the innovative approach of using PDT in treating bacterial infections. By integrating these elements, the study aims to provide insights into effective, biocompatible treatments for antibiotic-resistant bacteria.  The primary objective of this study is to synthesize and characterize AgNPs using butterfly pea extract and evaluate their effectiveness against S. aureus when combined with red laser irradiation.  Silver nanoparticles were synthesized using an environmentally friendly method that processes butterfly pea extract as the reducing agent for the synthesis of the nanoparticles.  Using UV-Vis spectrophotometry to track the creation of silver nanoparticles (AgNPs), it was determined that the butterfly pea extract was an effective source of nanoparticles. The particle size distribution and peak absorbance wavelength were determined by characterization utilizing a Particle Size Analyzer (PSA). Tryptic soy agar (TSA) plates were used to investigate the antibacterial activity of AgNPs against Staphylococcus aureus (S. aureus). The effectiveness of photoinactivation against S. aureus was evaluated by exposing AgNPs at a concentration of 1 mM to a red diode laser for 90 seconds. The results showed that the produced AgNPs had potential antibacterial capabilities when combined with red light therapy. The results demonstrated that the synthesized silver nanoparticles can effectively kill or inhibit the growth of Staphylococcus aureus (S. aureus) when exposed to a red diode laser for 90 seconds. The findings suggest that photodynamic therapy using green-synthesized AgNPs and red laser irradiation could be a promising approach to controlling bacterial infections like S. aureus. Further research is recommended to explore the underlying mechanisms of photoinactivation and to optimize treatment parameters for in vivo applications on experimental animals.